FAKTOR-FAKTOR YANG BERHUBUNGAN DENG SEKS PRANIKAH PADA REMAJA DI DESA SUSUKAN KECAMATAN SUMBANG - ., Minah; Pantiawati, Ika; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Unhealthy sexual behavior among unmarried adolescents in recent years is alarming symtoms. Research Type was analytic research with the cross sectional approach. Intake Sample with simple random sampling with the amount 70 respondent. Instrument Research in the form of questioner and analyses use the univariateÂ  and bivariate analysis with the test of chi square. From the result of chi square test with the knowledge of the relationship between premarital sexual behavior known to the pvalue 0,328, level of understanding of the religion known pvalue 0,002, the role of parents known the pvalue 0,000.There was no relationship between knowledge with premarital sexual behavior, and there was a significant relationship between the level of understanding of religion and the role of older people with premarital sexual behavior. Hoped religious leaders could improve his preaching among adolescents and parents should enhance the supervision of their teenagers. Keyword : premarital sexual behavior, adolescent